Combined medico‐surgical strategy for invasive sino‐orbito‐cerebral breakthrough fungal infection with Hormographiella aspergillata in an acute leukaemia patient. Issue 5 (6th March 2015) - Heiblig, M.; Bozzoli, V.; Saison, J.; Thomas, X.; De Croze, D.; Traverse‐Glehen, A.; Cosmidis, A.; Chidiac, C.; Ferry, T.; Alanio, A.; Bienvenu, A. L.; Dupont, D.; et al.
Summary Hormographiella aspergillata is a rare causative agent of invasive filamentous breakthrough infection, mostly arising after echinocandin exposure. We report a neutropenic patient who developed a severe sino‐orbito‐cerebral H. aspergillata infection while receiving empirical caspofungin, successfully controlled by an aggressive strategy associating surgical debridement and combined high‐dose regimen of antifungal drugs.